Species diversity and dispersal traits alter biodiversity spillover in reconstructed grasslands. Issue 9 (1st August 2019) - Sperry, Katie P.; Hilfer, Hayley; Lane, Ian; Petersen, Jessica; Dixon, Philip M.; Sullivan, Lauren L.
Abstract: Grasslands are among the planet's most imperilled ecosystems, largely because habitat conversion has caused extreme biodiversity loss. In response, managers and scientists aim to recreate grassland habitat, yet these reconstructed grasslands are often species‐poor and lose diversity through time. One potential mechanism to promote biodiversity in grasslands is spillover, or the targeted dispersal of species across habitat boundaries from areas of high to low biodiversity. There is potential for native species to disperse via spillover from high‐quality remnant habitat and establish in reconstructions, thus increasing biodiversity. However, plant dispersal and establishment are often context dependent, and the conditions that promote spillover in grasslands are largely unknown. Here we examine the contexts under which spillover can enhance biodiversity in grasslands. Specifically, we investigate whether the species richness of reconstructions and individual plant dispersal traits alter spillover. To do so, we surveyed plant species richness at reconstructed grasslands of varying diversity adjacent to remnant grasslands. We found that spillover from remnants supplies reconstructions with rare species that would otherwise not be present, but only in reconstructions with lower overall richness. Furthermore, spillover was more likely to occur for species with wind dispersed seeds than species with unassisted seed dispersal. Synthesis and applications. Our results show that the context dependency of both dispersal and establishment processes are critical to understanding when and where spillover can promote biodiversity in reconstructed systems. Understanding these contexts will help land managers leverage natural dispersal to mitigate biodiversity loss by anticipating which species are likely to arrive in reconstructions without assistance and when they are likely to establish. Abstract : Our results show that the context dependency of both dispersal and establishment processes are critical to understanding when and where spillover can promote biodiversity in reconstructed systems. Understanding these contexts will help land managers leverage natural dispersal to mitigate biodiversity loss by anticipating which species are likely to arrive in reconstructions without assistance and when they are likely to establish.